POLITICAL PARTIES AND PARTY DEVELOPMENT IN GEORGIA - DOLIDZE, Valerian (CENTRAL ASIA AND THE CAUCASUS, 2005)
The peaceful coup of 23 November 2003, otherwise known as the Rose Revolution, proved fatal for nearly all of Georgia’s political parties: only one of them—the United National Movement—gained weight at the expense of the others. Some of them were wiped away, while others were too shocked to recover promptly. This slowed down the country’s movement toward consolidated democracy, the road to which lies through strengthening several political parties. Despite the freedom of speech and political activity it enjoyed, the country failed to change the government by holding objective and fair elections. Georgia was not alone in the so-called gray zone: there are other states with no clear dictatorial or democratic biases. 1 The Rose Revolution itself is a product of half-baked democracy and the arrest ed transition process. It was precisely freedom of speech and political activity, the façade of democracy, that played the key role in the revolution. It is still too early to tell whether, since the Rose Revolution, Georgia has emerged from the gray zone, as the revolution considerably weakened not only the political parties and their political rivalry, but also the first shoots of civil society. The most active representatives of strong (according to Georgian standards) NGOs joined the new cabinet, thus laying bare their political nature. The United National Movement grew stronger, while other parties grew weaker. It was not administrative pressure that was responsible for this: politics followed its natural course due to the parties’ inability to catch the mood of the masses and adjust to it. The parties’ influence on the public is rather weak—public opinions are spontaneous—it is not the parties leading the masses, it is the masses leading them. The parties are unable to shape electoral behavior, therefore, to survive they must readjust their behavior to suit public sentiments. The Rose Revolution amply confirmed this. Mikhail Saakashvili grasped the popular sentiments and shaped his political strategy to match popular discontent and radicalism. This brought him victory.